Speech and chronological enunciation (a semiotic approach) - Cuculiza, María Nelly (1986)
Don Felipe Guaman Poma de Ayala, whose mother tongue was Quechua, writes in Spanish between the end of the 16th century and the beginning of the 17th century. His work, the New Chronicle and Good Government, is thus situated at the beginning of contact between the Andean peoples and the West, often showing a marked duality at all levels; It is this dual aspect that I wish to comment on in order to determine the forms it takes, the character of acculturation, its diversity and its consequences.